Metabolic syndrome and professional aptitude - Rębak, Dorota; Suliga, Edyta; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2015)
The development of civilisation has resulted in a growing problem of metabolic diseases, including metabolic syndrome. Scientific studies show that this disease is an epidemic of the 21st century. Metabolic syndrome is a collection of mutually related metabolic factors, such as obesity, impaired glucose tolerance, lipid disorders, arterial hypertension, and pro-inflammatory and prothrombotic state, increasing the risk of the development of atherosclerosis and type 2 diabetes, and their cardiovascular complications. Considering the scale of the prevalence of metabolic syndrome, the causes of its development and diagnostic criteria are the main contemporary directions of scientific research. The study presents an analysis of the relevant literature with respect to terminology, diagnostic criteria, and pathogenesis of metabolic syndrome. The second section of the study discusses the degree of epidemiological risk due to metabolic syndrome and its individual components among the adult Polish population. The effect of this phenomenon on professional competence is also taken into consideration.